2020
DOI: 10.1093/eurheartj/ehaa745
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of environmental pollutants for prevention of cardiovascular disease: it’s time to act

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
1
31
0
3
Order By: Relevance
“…catecholamines), which will be causing adverse changes in blood pressure, blood lipids and blood glucose. 2 As discussed earlier, a novel pathway via adverse changes in systemic inflammation or vascular inflammation only came to light recently 38 , 39 (Graphical Abstract). A study recently reported that the amygdala may be involved in processing the stress response via heightened arterial inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…catecholamines), which will be causing adverse changes in blood pressure, blood lipids and blood glucose. 2 As discussed earlier, a novel pathway via adverse changes in systemic inflammation or vascular inflammation only came to light recently 38 , 39 (Graphical Abstract). A study recently reported that the amygdala may be involved in processing the stress response via heightened arterial inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…In the setting of traffic noise, a variety of mitigation strategies are proposed, such as developing and using low-noise tires, quiet engines, and breaks, applying quiet surfaces, installing noise barriers in densely populated areas, introducing adequate speed limits (in particular during sleeping hours), minimizing the overlap of traffic routes and housing zones, introducing night bans, installing sound-reducing windows, and placing sleeping rooms towards the quiet side of the house. Current approaches to mitigate air pollution exposure are mainly focused on personal actions like using air filtration or face masks, avoiding exposure by changing travel routes, staying indoors/closing windows, modification of outdoor activities, and keeping distance from areas where higher concentrations of air pollutants are expected, such as major roadways [ 180 ]. In any case, large-scale macro interventions in the long run, on a political and societal level that question the way we work and live are clearly needed to achieve sustainable success.…”
Section: Discussionmentioning
confidence: 99%
“…The central government in China, like many other developing countries, has adopted a green environment-friendly policy to help sustaining economic transition and modernization [42]. However, in the coming 1-2 decades, PM2.5 air pollution could still exceed the safe level of <20µg/m 3 advocated by WHO, and accordingly would pose an important environmental problem compared with many countries in the western world [43]. While traditional risk factors should be dealt with and optimally addressed, our present study proposes, in addition, emphasis on both air pollution and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%